Quantifying the relationship between the structure of competition performance and fitness structure in racket sports (squash, badminton, tennis). - Krasilschchikov, Oleksandr (Universiti Sains Malaysia, 2015)
Final outcome of competitions - result was always the final criteria of the effectiveness of a team/individual preparation towards the competition. During the last decade, researchers got into the quest on the performance contributing factors belonging to physiology (Baechle, T.R., & Earle, R.W. (2000), psychology (Petruzello S. (2001), biomechanics (Coleman, S, 1998) and so on. But only recently performance analysis in the real game/match situations became independent and quite popular field of research (Franks and Hughes, 2008). Literature review however, revealed that researchers in fact never opted to combine the above human performance domain under one major objective - manipulation of competition performance variables and effectiveness. As the result of the current research, the following major outcomes were achieved: The major performance variables identified influencing performance outcome in squash, and table tennis; Match performance components were quantified for the national/international level squash and table tennis players. Physical fitness components influencing performance outcomes quantified for the national and international squash, and table tennis players. The relationships are established between fitness and performance outcomes in squash. Training programmes developed and assessed on forming the desired competition performance outcome in squash and tennis by manipulating physical fitness of the players through variations of periodesed training.